The Influence of Audit Committee Characteristics on the Quality of Financial Reporting from a Corporate Governance Perspective - Dewi, Yuli (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The quality of financial reporting is a crucial element in achieving transparency and accountability within the framework of Good Corporate Governance (GCG). Numerous financial scandals have demonstrated that weaknesses in internal oversight, particularly within audit committees, can lead to financial misreporting and loss of stakeholder trust. This study aims to analyze the influence of audit committee characteristics—namely independence, financial expertise, committee size, and meeting frequency—on the quality of financial reporting from a corporate governance perspective. The research employs a qualitative approach using a systematic literature review method. Secondary data were collected from peer-reviewed journals, conference proceedings, and official regulatory reports indexed in Scopus, ScienceDirect, Emerald Insight, SpringerLink, and Google Scholar, covering publications from 2010 to 2025. The data were analyzed using thematic content analysis to identify patterns, relationships, and governance implications. The findings indicate that audit committee independence and financial expertise play a dominant role in enhancing financial reporting quality by reducing earnings management and improving oversight effectiveness. Additionally, an optimal committee size and frequent, well-structured meetings contribute to better monitoring, transparency, and accountability. Overall, the study concludes that the integration of audit committee characteristics is essential for strengthening financial reporting quality and supporting effective corporate governance practices, particularly in emerging market contexts.